Family Caregivers' Experiences of Caring for Cancer Patients In Tertiary Care Hospitals, Islamabad Pakistan - Batool, Tahira; Dhamani, Khairunnisa; Habibullah, Gulzar; Hamid, Nazma (MPI Press, 2024)
Background: Cancer gravely affects the physical, psychological, emotional, and economic conditions of not only the patient who has been afflicted but also the friends and loved ones, especially those who are involved in caregiving. Extended hospital stays place greater demands on caregivers, highlighting the crucial role of family caregivers (FCGs) as primary patient support. Purpose: This study aimed to explore the experiences of FCG of cancer patients who are admitted to the tertiary care hospitals of Islamabad, Pakistan. Methods: A qualitative exploratory descriptive study design was used. The sample size was 16 FCGs of cancer patients from public and private hospitals. Data collection involved face-to-face interviews. Data was analyzed by using the following sequential process of data analysis. Result: FCGs experience significant physical and emotional challenges while caring for critically ill cancer patients. They endure hardships of caregiving by providing physical care and a few of the imposed tasks like drawing blood and intravenous infusions. The emotional toll is profound, leading to psychological distress and neglect of their well-being. The financial strain impacted the education of children of FCGs, the loss of jobs, and the selling of property to manage cancer treatment. To cope with these challenges, FCGs relied on the teachings of their faith, offering religious prayers, and diverting minds using social media. FCGs emphasized the need for improved communication and attitudes of healthcare staff. Conclusion: This study highlighted the physical, emotional, and financial hardships endured while providing care. However, their personal needs often go unnoticed and may become ineffective in supporting patients. Therefore, healthcare professionals must develop targeted support programs for FCGs.